Correlation of Causality of Salt Imports and Domestic Salt Prices - Fauzan Faisal; Mohammad Wahed (Cita konsultindo, 2025)
Salt is an important commodity for households and industries in Indonesia, with increasing national needs. However, domestic production is still limited, so dependence on imports is the main challenge. This study analyzes the causal relationship between salt imports and domestic prices using the Granger causality test with secondary data from the Ministry of Maritime Affairs and Fisheries (KKP) and the Central Statistics Agency (CSA) for the 2011–2023 period. The methods used are Vector Autoregression (VAR) and Vector Error Correction Model (VECM) to test long-term and short-term relationships. The results show that in the short term, salt imports do not have a direct causal relationship with domestic prices, but in the long term, there is a balance relationship between the two. In addition, domestic salt prices also do not directly affect import volumes in the short term, but contribute to import variability in the long term. These findings underscore the importance of balanced import policies to maintain price stability, protect local salt farmers, and meet the needs of the industry in a sustainable manner.